2017
DOI: 10.1037/rep0000161
|View full text |Cite
|
Sign up to set email alerts
|

Social-cognitive predictors of vocational outcomes in transition youth with epilepsy: Application of social cognitive career theory.

Abstract: The research findings provide support for the use of the SCCT framework to identify predictors of work participation and to provide guidance for designing customized vocational rehabilitation services and career development interventions for individuals with epilepsy in the transition from adolescence to adulthood. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 78 publications
(116 reference statements)
0
14
0
2
Order By: Relevance
“…Five of the 31 included studies utilizing outcome measures to collect data/information about work participation. These measures included the Assessments of Life Habits [24], the Work Experience Survey [25], the Career Mastery Inventory [25], the Beach Centre Family Quality of Life Scale [26], the Developmental Behaviour Checklist adult version [26], the Index of Social Competence [26], the Stages of Change work Participation Scale [27], and the Vocational Integration Inventory [28]. Only one standardized measure addressed all aspects of the environment; the Measure of the Quality of the Environment [24], while the others focused on a single-domain measure of the environment such as the Family Support questionnaire [26].…”
Section: Descriptive Summary Of the Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Five of the 31 included studies utilizing outcome measures to collect data/information about work participation. These measures included the Assessments of Life Habits [24], the Work Experience Survey [25], the Career Mastery Inventory [25], the Beach Centre Family Quality of Life Scale [26], the Developmental Behaviour Checklist adult version [26], the Index of Social Competence [26], the Stages of Change work Participation Scale [27], and the Vocational Integration Inventory [28]. Only one standardized measure addressed all aspects of the environment; the Measure of the Quality of the Environment [24], while the others focused on a single-domain measure of the environment such as the Family Support questionnaire [26].…”
Section: Descriptive Summary Of the Studiesmentioning
confidence: 99%
“…Only one standardized measure addressed all aspects of the environment; the Measure of the Quality of the Environment [24], while the others focused on a single-domain measure of the environment such as the Family Support questionnaire [26]. Other studies identified environmental factors in the workplace by either relying on data from national surveys or by using their own questionnaires/surveys without any psychometric tests to validate them [27][28][29][30][31][32]. The majority of the included studies (71%) examined more than one facet of the ICF environmental domains with regards to work participation.…”
Section: Descriptive Summary Of the Studiesmentioning
confidence: 99%
See 3 more Smart Citations